Correlation Between Synovial Fluid Biomarker Concentrations and Bone Marrow Edema Lesion Volume in Patients with Acute ACL Ruptures. Issue 7 (30th July 2018) - Anil, Utakarsh; Werner, Jordan; Jejurikar, Neha; Kenny, Lena; Pham, Hien; Liu, James; Mastio, Michele; Burke, Christopher; Strauss, Eric Jason
Objectives: Bone marrow edema lesions (BMELs) frequently occur following acute anterior cruciate ligament (ACL) rupture secondary to the pivot-shift mechanism of injury. The aim of the current study is to evaluate whether synovial fluid biomarker concentrations are associated with bone edema lesion volume as measured by magnetic resonance imaging (MRI) in patients undergoing ACL reconstruction. Methods: A total of 53 patients (26 females, 27 males, mean age 35.0 years [range 18-59]) undergoing ACL reconstruction with MRI knee scans available for analysis participated in the study. Synovial fluid was collected intra-operatively and analyzed for 10 biomarkers hypothesized to be involved in inflammation and post-traumatic osteoarthritis. BMELs were identified on MRI and their volumes (cm3) were quantified on two independent occasions using FireVoxel imaging software for image segmentation and region-of-interest drawing. The correlation between synovial fluid biomarker levels and BMEL volume was evaluated using Spearman's correlation coefficient. Measurement reliability was assessed using intraclass correlation coefficient (ICC) analysis. Significance was set at p<0.05. Results: Mean time from initial injury to synovial fluid aspiration was 319 days (std. dev. 892; range 15-4320) and mean lesion volumes were: tibial=6.4 cm3 (range 0-38.6); femoral=5.8 cm3 (range 0-34.0); total=12.2 cm3 (range 0-50.5). Measurement reliability of BMEL volume was excellent [ICC(2, 1)=0.968 (CI 0.945-0.981)]. Analysis of patients with MRI within 30 days of injury (n=35) showed increased tibial BMEL volume was significantly (p<0.05) correlated to decreased concentrations of interleukin (IL)-6 (ρ=-0.481), IL-1 receptor antagonist (ρ=-0.361), and vascular endothelial growth factor (VEGF) (ρ=-0.397) and increased time from injury to aspiration was correlated to decreased concentration of IL-6 (ρ=-0.463), monocyte chemotactic protein-1 (ρ=-0.453), VEGF (ρ=-0.457), IL-1Ra (ρ=-0.448), and matrix metalloproteinase (MMP)-3 (ρ=-0.426). However, among all patients, synovial fluid biomarker levels had no significant correlations to BMEL volume or time from injury to aspiration. Conclusion: Analysis of synovial fluid at the time of ACL reconstruction demonstrated that increased volume of injury-associated BMEL on MRI performed within 30 days of initial injury was significantly correlated to decreased concentrations of pro-inflammatory and growth factor cytokines. These findings suggest that the impact of the pivot-shift mechanism of injury and presence of BMEL may have an affect the local joint microenvironment. Table 1. Biomarker Values and Correlation with Bone Edema Lesion Size in Patients with MRI Within 30 Days of Initial Injury Number of samples Mean (pg/ml) Standard Deviation (pg/ml) Spearman correlation with lesion size Tibia Femoral Total RANTES 35 591.07 1972.12 -0.03 -0.10 -0.11 IL-6 35 177.69 493.79 -0.48* 0.21 -0.19 MCP-1 35 366.15 213.50 -0.31 0.17 -0.12 MIP-B 35 50.98 85.41 -0.18 0.12 -0.03 VEGF 35 328.79 303.13 -0.39* 0.26 -0.13 TIMP1 35 369909.29 156363.48 -0.07 0.10 -0.05 TIMP2 35 93235.02 96963.73 0.13 -0.06 0.07 IL-1Ra 35 418.07 1754.43 -0.36* 0.00 -0.26 MMP3 35 3373710.56 3763593.71 -0.13 0.31 0.04 bFGF 35 48.41 99.94 0.11 -0.22 -0.06 *p<0.05